Determinants of Farm Households’ Participation in Microfinance Program and Its Impact on Their Livelihoods: The Case of Boneya Boshe Woreda of East Wollega Zone, Oromia, Ethiopia - Mekonen, Tolera; Mulatu, Gemechu (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Microfinance is the institution that provides access to various financial services such as credit, savings, leasing to low-income clients including consumers and the self-employed, who traditionally lack access to banking and related services. The objective of this study was to identify factors that affect farm households’ participation in microfinance program and evaluate its impact on their livelihoods (Income, Saving and Asset). In order to achieve these objectives, both primary and secondary data were collected. Primary data was collected using semi-structured questionnaire and interview. While, secondary data was collected from different published and unpublished documents. Multi-stage stratified sampling technique and systematic random sampling technique were followed to reach 364 sample respondents out of 4,045 total farm households’ of the selected kebeles. Descriptive, inferential and econometric methods were used to analyze the data. Binary Logit regression model and Propensity Score matching technique were applied by using stata software version 15. Logistic regression result indicates that program participation was significantly and positively affected by family size, education level, farm size, risk perception, extension visit and training access of household head whereas distance of household home from microfinance office have negative effect. The result of sensitivity test using of rosenbaum bounds also implies that the estimated impact result was insensitive to unobserved characteristics. Furthermore, PSM result indicates that microfinance program has a significant and positive impact on income, saving and asset of participant households. Finally, the study recommends that microfinance institutions and other concerned stakeholders should broaden their outreach and expand its access to rural areas in enhancement of rural farm households’ livelihoods.